Self-management of a musculoskeletal condition for people from harder to reach groups: a qualitative patient interview study. Issue 25 (4th December 2019) - Adams, Jo; Lowe, Wendy; Protheroe, Joanne; Lueddeke, Jill; Armstrong, Ray; Russell, Cynthia; Nutbeam, Don; Ballinger, Claire
Abstract: Background: This study recorded the functional health literacy levels of people with musculoskeletal (MSK) conditions from harder to reach groups and explored their experiences in engaging with health care professionals to self-manage their MSK condition. Methods: We recruited participants, identified by key health and social care contacts as likely to have lower health literacy levels, and used semi-structured interviews to collect data. Thematic analysis was used to identify the main key themes arising from the transcribed interviews. Results: Eighteen participants were identified and recruited from harder to reach community populations, 10 were scored as having inadequate functional health literacy on the Short Form Rapid Estimate of Adult Literacy Measure. Three themes were identified in relation to participants' experiences of MSK self-management approaches: engaging with health care services; interpreting the health care providers' message; and facilitating participation in MSK self-management. Conclusions: Our findings indicate that people with a MSK condition, from harder to reach groups, experience multi-morbidity, find health care systems complicated and hear from health care professionals that their MSK condition cannot be cured. People interpreted that a lack of cure meant that nothing could be done to help their MSK pain. Engaging with self-management strategies was not seen as a priority for our participants. Strategies to simplify health communication, more time to process health information and supportive social networks helped our participants to understand and manage their MSK health on a day-to-day basis. Implications for Rehabilitation: MSK conditions are long term and prevalent in the UK with substantial impact on people's daily life. Currently self-management strategies for MSK conditions are poorly communicated and many patients believe that nothing can be done to help their MSK pain. Good clinician communication that supports self-management is needed so that key messages can be effectively understood and used by patients with a range of literacy skills. Health services need to be even more accessible to help all individuals from a range of backgrounds better self-manage their MSK conditions.